Assessment and Variation of Water Quality in Urban Distribution Networks: From Reservoir to Faucet - Eunhye Jeong; Kyung-Yup Hwang; Sumin Lee; Kwangjun Jung; Hyunjun Kim (Engineering Proceedings)
This study focuses on evaluating the spatiotemporal variations in water quality across a potable water distribution network in D City, South Korea, spanning from a reservoir to a large consumer’s tap. Utilizing water quality sensors installed at strategic points (the reservoir, District Metered Area inlet, consumer inlet, tank outlet, and tap), this research observes real-time changes in parameters such as chlorine concentration, turbidity, temperature, pH, and electrical conductivity. The investigation, conducted from 25 January 2024 to 4 February 2024, identifies significant trends such as the gradual decrease in chlorine concentration with distance and time, an increase in turbidity and temperature towards the consumer end, and variations in electrical conductivity. These observations suggest that there is an influence of pipe material interactions, water stagnation, and usage patterns on water quality. This study contributes to understanding the dynamic nature of tap water’s quality, highlighting the need for continuous monitoring and research to manage water quality effectively in urban distribution networks.